(untitled) (Journal of Nematode Morphology and Systematics, 2012)
Six species of the superfamily Rhabditoidea, namely Cruznema tripartitum, Diploscapter coronatus, Pelodera punctata, P. strongyloides, Rhabditella axei and Rhabditis cf. terricola, are described from natural areas in Tehran province (Iran). All of them, except Diploscapter coronatus, are reported for the first time from Iran. Descriptions, measurements, illustrations, including SEM pictures, are provided for the six species. A list of Pelodera species is also given as well as a key to their identification. Pelodera pheropsophi is transferred to Rhomborhabditis.